Association of necrotizing enterocolitis with antimicrobial exposure in preterm infants <32 weeks gestational age:A multicenter prospective case-control study - Pei, Xiaojing; Gao, Yujun; Kou, Yan; Ding, Yanjie; Li, Dan; Lei, Peng; Zuo, Lili; Liu, Qiongyu; Miao, Naiying; Reddy, Simmy; Yu, Yonghui; Sun, Xuemei (Frontiers in Pharmacology, 2022)
Objective: To assess the risk of necrotizing enterocolitis (NEC) and to explore the relationship between antibiotic exposure and disease occurrence in a large prospective birth cohort. Method:Based on a prospective birth cohort, the study collected hospitalization data of very preterm infants (gestational age <32 weeks) from January 2018 to June 2021 via the China Northern Neonatal Network (SNN). Infants diagnosed with NEC ≥ stage II were included in the case group, and each case was matched for gestational age (GA) and birth weight, and the risk factors for NEC were determined by statistical analysis. Results:A total of 6425 very preterm infants (VPIs) were included in this study, and 167 (2.60%) were diagnosed with with NEC ≥ II stage. The study included 984 extremely preterm infants (EPIs) , including 50 (5.08%) infants diagnosed with NEC ≥ stage II. In the matched case-control study, subjects had total antibiotic DOT for 9015 days, of which broad-spectrum antibiotic (BSA) DOT accounted for 76.76%. Third-generation cephalosporins were the most frequently prescribed. The ASI per antibiotic days in the case group was higher, and it was an independent risk factor for the occurrence of NEC (P=0.001, OR=1.131). Conclusion: The cohort of VPIs was overexposure to antibiotics, and it was associated with NEC.